2019
DOI: 10.1016/j.energy.2019.116366
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Kullback-divergence-PCA for intelligent mismatch detection and power quality monitoring in grid-connected rooftop PV

Abstract: In parallel to sustainable growth in solar fraction, continuous reductions in Photovoltaic (PV) module and installation costs fuelled a profound adoption of residential Rooftop Mounted PV (RMPV) installations already reaching grid parity. RMPVs are promoted for economic, social, and environmental factors where they not only improve energy performance and reduce greenhouse effects but also contribute to bill savings.RMPV modules and energy conversion units are frequently subject to various types of anomalies wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
17
0
2
Order By: Relevance
“…where P, P 0 are distribution functions in measure space Ω. Many scholars have studied the DRO based on KL divergence [31][32][33][34], and they put forward some reformulation methods in the research. In these studies, KL divergence has been used to solve problems such as unit commitment, and showed its advantages.…”
Section: Dro Model Based On Kl-divergencementioning
confidence: 99%
See 3 more Smart Citations
“…where P, P 0 are distribution functions in measure space Ω. Many scholars have studied the DRO based on KL divergence [31][32][33][34], and they put forward some reformulation methods in the research. In these studies, KL divergence has been used to solve problems such as unit commitment, and showed its advantages.…”
Section: Dro Model Based On Kl-divergencementioning
confidence: 99%
“…In general, the data are not fully utilized because the distribution knowledge contains more information than moments. Motivated by the deficiency of the moment-based DRO method, reference [24][25][26][27][28][29][30][31][32][33][34] investigated the distance-based DRO method. Usually, in a distance-based DRO model, the ambiguity set is constructed by probability distribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing the impact of process variable selection on PCA monitoring performance, Jiang et al used the genetic algorithm (GA) to select a subset of variables that were most relevant to each type of fault to divide the process data into corresponding sub-blocks, and then established a multi-block monitoring model [25]. Bakdi et al proposed that apply multi-block PCA to extract dominant transformed components (TCs), and most sensitive components are selected for the fault detection [26]. Although the monitoring performance of these multi-block monitoring methods has improved when compared to traditional monitoring methods, the dynamic characteristics of the process are still ignored, resulting in the unsatisfactory monitoring results.…”
Section: Introductionmentioning
confidence: 99%